State regulation of socio-economic development in a pandemic (Journal of Economic Research & Business Administration, 2021)
During the economic crisis caused by the coronavirus pandemic (COVID-19), the governmentsof the countries implemented measures in various areas of domestic policy – financial, monetary andsocial. The measures were of an extraordinary nature, providing for the solution of such tasks as thepreservation of business and employment support, social protection and public health protection. Forobvious reasons, in most countries of the world, all means have been used to fight the pandemic. Inthe budgetary sphere, extraordinary and far-reaching measures have been taken regarding taxes andexpenditures, designed to save lives, support the population and businesses, and create conditions foreconomic recovery.The article reveals the current economic and social consequences of the COVID-19 pandemic basedon a literature review, as well as identifies strategic actions of state regulation to solve problems after theend of the pandemic in the field of digital technologies and expanding access to the Internet, revisingthe system of social benefits. The necessity of introducing a progressive tax system has been substantiated.Particular attention is paid to professional orientation of the population, taking into account theconsequences of the pandemic and current trends in the labor market and the functions of employment centers, as well as the importance of training in accordance with skills for life and adaptation to changingrealities.The object of the research is the socio-economic processes in the Republic of Kazakhstan duringthe pandemic. In the country, an unprecedented situation has developed and established itself in 2020-2021, for which both the government and the population were not prepared. Day by day, the numberof fatal cases is increasing, a new strain of the virus has appeared, and the vaccination is not giving theexpected results. The government of the country needs to take tough and effective measures. All thissubstantiated the relevance of the chosen research topic.Key words: social projects, COVID-19, macroeconomics, labor market, education, governmentregulation, vocational guidance.